Industrial Sunrise? The Chrysler Bailout, the State, and the Re-industrialization of the Canadian Automotive Sector, 1975-1986 - Anastakis, Dimitry (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2007)
After 1980 deindustrialization was the prevailing condition in the North American automotive industry—but not in Canada. Much of that difference was due to an aggressive federal intervention that demanded investment and production from foreign automakers. Using Chrysler as a case study, the paper asserts that state policies such as the 1980 bailout and the 1965 Canada-U.S. Auto Pact actually led to a re-industrialization of the Canadian sector. The paper challenges older dependency theories that assume deindustrialization, and recent work that focuses upon worker activism, as the reason that Canada's industrial heartland did not rust.